The Effects of Using the Reciprocal Teaching Strategy in the Literary Texts Teaching on Developing the Literary Appreciation Skills of the Third Grade Intermediate Female Students - Fahad A. Al- Baker (Sultan Qaboos University, 2014)
The study aimed at identifying the effects of using the reciprocal teaching strategy in the literary texts teaching on developing the literary appreciation skills of the third grade intermediate female students. The study was conducted on a random sample of the third grade intermediate female students (n=48) in Riyadh, KSA that was divided into two groups: The experimental group (n= 24) studied the literary appreciation skills using the reciprocal teaching strategy whereas the controlled (n=24) studied the same material but using the traditional method of teaching. The study employed a list of the literary appreciation skills appropriate for the third grade intermediate level, and a test to measure their mastery of those skills. The pre- and post-treatment application of the research instruments revealed that there is weakness in the students' mastery level of the literary appreciation skills, and that most of the literary appreciation skills require development. The study also revealed that there are statistically significant differences between the experimental group and the controlled group, the former excelled the latter reflecting an efficacy of using the reciprocal teaching strategy. In view of the findings of the study, some suggestions and recommendations were proposed for future research.